Design of Wireless Garbage Monitoring System using Rasspberry pi - Abdulwahab, Mortada Mohammed; Zain Elabdi, Bahaa A; Ahmed, Asmaa; Osman, Osman A (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2021)
The garbage volume increases proportionally to the degree of progression in the economy of a country: It increases rapidly in the countries, where there are rapid increase of housing capacity and industrial locations. Garbage is considered a big challenge facing by all countries. It affects human health by causing diseases. The objective of this study is to design a wireless monitoring system for garbage containers, that assists to reduce the risks of overflowed garbage that spread out of the container. The design of the system is based on Raspberry Pi and consists of ultrasonic sensor with alarm circuit. Moreover, the design provides wireless monitoring of the garbage in the trash container via Wi-Fi technology. It includes database system for saving data. The system was tested experimentally in two different operating cases: when the container was empty and when it was full. The overall results reveal that the system works correctly, and all the obtained results were shown in the web page. The results proved that this monitoring system can help in reducing the problems of garbage problems by providing continuous monitoring of the garbage container status.